Solving the calcium gluconate shortage in real‐time: Mistakes made and lessons learned. Issue 4 (23rd January 2019) - Williams, Lance A.; Sikora, James; Richardson, Carole; Rigi, Mohammed; Boshell, Nick; Palmer, Lakeyra; Dunn, Sondra; Slover, Terry; Peavey, Daniel; Guillory, Bryan; Marques, Marisa B.
Abstract : Purpose: During a national shortage of calcium gluconate, we switched to calcium chloride for routine supplementation for peripheral blood stem cell (PBSC) collections. Subsequently, we analyzed the postprocedure ionized calcium level, as we aimed for an equivalent result compared to before the shortage. Methods: Pharmacy representatives helped us to find an "equivalent" substitute for calcium gluconate at 46.5 mEq in 500 mL normal saline, infused at 100 mL/hour. After instituting a presumably comparable protocol using calcium chloride (40.8 mEq in 250 mL normal saline at a rate of 100 mL/hour), we reviewed ionized calcium results post‐PBSC procedures to compare with those obtained with calcium gluconate. Having noticed a difference in the mean values, we adjusted the rate of calcium chloride to reach our desired outcome. Results: Twenty‐seven procedures were analyzed on 15 unique patients. We used the Spectra OPTIA with a whole blood: anticoagulant ratio of 13:1. Ionized calcium levels post‐PBSC collection with the first calcium chloride protocol were significantly higher ( P  = 0.003) in nine patients treated. Subsequently, we decreased the calcium chloride infusion rate to 75 mL/hour and achieved similar mean levels to calcium gluconate ( P  = 0.382). Conclusion: Changes in replacement fluids for apheresis procedures can be complex, particularly when dealing with electrolytes that could be clinically significant at critically high or low levels. Once we recognized the need to take into account the amount of elemental calcium infused, we achieved the desired postprocedure ionized calcium results. This study can serve as a lesson for future shortages of infusions used during apheresis procedures.